A novel overvoltage protection scheme for power electronics switching under differential surge conditions - Teik Hua Kuan; Kuew Wai Chew; Kein Huat Chua (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The proposed scheme is employed for the efficient operation of a DC-DC-based buck converter. This protection scheme shows the optimal placement of a varistor in the power electronics converter side under different surge conditions. Advanced varistors have excellent electrical material properties and electrothermal behavior for the enhancement of power absorption capability. Varistors have been examined widely in the last four decades that are employed for surge protection applications. The advantage of power surge protection using varistor-based power devices is vital due to the great sensitivity of the equipment integrated into the grid and emerging power electronics-based DC systems with low and high voltage ratings. In this research, a varistor can be placed to protect the switching devices such as MOSFETs in power electronic-based buck converter side due to uncertain overvoltage under differential surge. The proposed MATLAB simulation study shows the peak voltage stress on the grid due to the surge and its enhancement scheme.